VOCATIONAL EDUCATION AND PRODUCTIVITY: A MACROECONOMIC AND EDUCATOR-BASED ASSESSMENT - Rusinov, Stoycho; Vasilev, Iliyan (LPPM Universitas Jambi, 2025)
This study explores the intricate relationship between vocational education and training (VET) and national productivity in Bulgaria through a multidimensional analysis that integrates macroeconomic data with institutional-level perspectives. Employing a mixed-method design, it combines national time-series data from 2003–2023 with survey responses from 63 VET educators in information technology and engineering. Quantitative analysis using total factor productivity (TFP) and labor productivity decomposition, supported by Granger causality tests, reveals a unidirectional link in which productivity growth drives VET participation, but not vice versa indicating that Bulgaria’s VET system struggles to convert economic expansion into human capital enhancement. Qualitative findings highlight systemic barriers, including outdated curricula, inadequate digital infrastructure, weak labor market alignment, and limited industry collaboration. Despite educators’ high self-rated competence, the institutional mechanisms for feedback and adaptation remain underdeveloped, resulting in a structural disconnect between educational provision and economic demand. The novelty of this study lies in its integrated macro–micro analytical approach, which bridges national productivity trends with educator-level realities—an underexplored nexus in the context of Central and Eastern Europe. By merging economic modeling with pedagogical insights, this research advances a more comprehensive understanding of how VET systems contribute (or fail to contribute) to national productivity. The study concludes with targeted policy recommendations, including the implementation of European quality assurance frameworks (EQAVET, ECVET), modernization of training programs, and investment in sustainable partnerships between VET institutions and industries to foster inclusive, innovation-driven economic growth.